Penerapan Algoritma Genetika Dalam Efisiensi Persediaan Bahan Baku Mebel Di UD. Mebel Jati - Harminto Mulyo (Jurnal Rekognisi Akuntansi, 2018)
Efficiency in determining the amount of inventory or raw material needs is an important issue for a company. Like other companies, furniture is also a company or industry that processes wood basic materials into household furniture such as cabinets, tables, chairs, and so on. The raw material for furniture is wood, and the availability of wood in the market is quite high and not always available. So furniture needs to be prepared by estimating the need for raw materials. With a good inventory system, furniture will get optimal profit. Genetic Algorithm is applied in optimizing the estimation of furniture raw materials to provide maximum profit by saving inventory costs. Genetic Algorithm used method of extended intermediate crossover, mutation, calculate the value of fitness and selection. In this study, there are 12 chromosomes which are furniture production data within a period of 12 months. The chromosome representation used is discrete decimal encoding. And each chromosome has genes 1-7 which is the product type. The optimal solution obtained from a population size of 100 populations, the combination of crossover and mutation is 1 and 1. With the highest fitness value of 45.00.